The Implementation of Justice Value in the Use of Electronic Certificate Data - Yovita Arie Mangesti (Fakultas Hukum, UPN Veteran Jawa Timur, 2022)
Land-related problems are found widely in Indonesia today, particularly related to the National Land Affairs Agency’s data of land unregistered and with no deed or double deed. Thus, government should solve them first to obtain the number of land because the data is different from the actual fact. It is related to the certificate inconsistent with dimension or the object of dispute in the Court. It means that the land deed or certificate no longer guarantees law certainty to the people. Minister of Agrarian Affairs and Spatial Planning/Chairperson of Land Affairs Agency’s Regulation Number 1 of 2021 concerns Electronic Certificate. The result of discussion shows that the electronic system-based land registration will yield electronic document as the output, i.e. electronic certificate that will benefit the people through providing easy access to digital data, evidence of land ownership, and foundation of law certainty guaranty over land ownership right, and freedom from land certificate falsification, legitimate legal evidence, and the expansion of legitimate evidence corresponding to procedural law enacted in Indonesia, constituting the foundation of justice, law certainty, and benefit guaranty to Indonesians.